Investigating the effects of brain stimulation on the neural substrates of inhibition in patients with OCD: A simultaneous tDCS – fMRI study - Daniela Rodriguez-Manrique; Hanyang Ruan; Chelsea Winkelmann; Julian Haun; Sandra Gigl; Götz Berberich; Claus Zimmer; Kathrin Koch (Translational Psychiatry)
Abstract Inhibition deficits constitute a core characteristic of obsessive-compulsive disorder (OCD). There is evidence in healthy individuals that transcranial direct current stimulation (tDCS) of the pre-supplementary motor area (pre-SMA) leads to a significantly improved inhibition performance. Against this background we investigated the effects of pre-SMA tDCS on inhibition performance and the underlying neural correlates in patients with OCD. Using a double-blind, randomized, sham-controlled, cross-over design (i.e., tDCS sham vs. tDCS stimulation) we investigated the effects of 2 mA anodal tDCS stimulation of the right pre-SMA in a sample of 47 OCD patients. The present study is, to our best knowledge, the first study applying concurrent tDCS-fMRI in patients with OCD. tDCS was applied using the MRI-compatible NeuroConn DC-Stimulator which allowed for a concurrent stimulation, while patients performed an inhibition (i.e., Stroop) task in a 3 T MRI. Imaging data were analysed using a multivariate partial least squares (PLS) approach. tDCS stimulation (vs. sham) was associated with increased activation in a fronto-parieto-cerebellar network comprising, amongst others, the precentral, middle frontal and inferior frontal gyrus, the anterior cingulate and the superior parietal lobe. On the performance level, tDCS stimulation (vs. sham) was linked to an improved inhibition performance in terms of an increased percentage of correct responses in the Stroop task. Present results indicate that tDCS in patients with OCD goes along with an improved inhibition performance as well as activation increases in regions known to be involved in inhibition, motor, and cognitive control. Thus, our findings suggest that tDCS might be a promising method to improve specific impairments in OCD.